PENGEMBANGAN MEDIA PUPPIM PADA MATERI PERKALIAN BILANGAN CACAH DI KELAS III SDN NO. 75 KOTA TENGAH - Sari, Rani Puspita; Abdullah, Gamar; Marshanawiah, Andi; Aries, Nur Sakinah; Assel, Hadi Yamin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research was motivated by the low level of students' understanding of the basic concept of multiplication, particularly in the topic of whole number multiplication. The aim of this research was to develop PUPPIM learning media that meet the criteria of validity, practicality, and effectiveness for teaching whole number multiplication in Grade III at SDN No. 75 Kota Tengah, Gorontalo City. The research employed a development method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects were 21 Grade III students. In the feasibility test, PUPPIM was validated by experts. The combined validation results from media, content, and user experts reached 93,1%, categorized as